BumbAR: Multimedia Authoring Through Augmented Reality - Mendes, Paulo R. C.; Soares Neto, Carlos de S. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2019)
This work describes the evolution of an approach based on augmented reality for authoring multimedia presentations. The BumbAR approach is based on the NCM model and explores the use of augmented reality and real-world objects (markers) as an innovative user interface for describing the behavior and relationships between the media objects that are part of a multimedia presentation. It was evaluated through a qualitative study based on the TAM model. The qualitative study aimed at evaluating users’ attitude towards using BumbAR. The results showed that the participants found that the proposed approach is both useful and easy-to-use, but comments made by them showed the need of including new functionalities in the BumbAR tool, which are described in this paper.